ANALYSIS OF THE INTERPRETATION OF THE SEA IN THE SPONGEBOB CARTOON - Pen Siau Hong; Assaidatul Husna (Puslitabmas Batam Tourism Polytecnic, 2024)
This analysis aims to highlight the social message related to marine pollution conveyed through the cartoon